Epithelial expression of interleukin‐37b in inflammatory bowel disease. (18th April 2013) - Imaeda, H.; Takahashi, K.; Fujimoto, T.; Kasumi, E.; Ban, H.; Bamba, S.; Sonoda, H.; Shimizu, T.; Fujiyama, Y.; Andoh, A.
Summary Interleukin (IL)‐37 is a member of the IL‐1 cytokine family. We investigated IL‐37b expression in the inflamed mucosa of inflammatory bowel disease (IBD) patients. Furthermore, we analysed IL‐37b expression in human colonic epithelial cells. The human colonic epithelial cell line T84 and human colonic subepithelial myofibroblasts (SEMFs) were used. IL‐37b expression in the IBD mucosa was evaluated by immunohistochemistry. IL‐37b mRNA and protein expression were determined by real time‐polymerase chain reaction (PCR) and Western blotting, respectively. IL‐37b was not detected in the normal colonic mucosa. In the inflamed mucosa of IBD patients, epithelial IL‐37b expression was increased markedly. In ulcerative colitis (UC) and Crohn's disease (CD) patients, IL‐37b expression was enhanced in the affected mucosa. In the intestinal epithelial cell line T84, the expression of IL‐37b mRNA and protein was enhanced by tumour necrosis factor (TNF)‐α. This IL‐37b induction by TNF‐α was mediated by nuclear factor (NF)‐κB and activator protein (AP)‐1 activation. Furthermore, IL‐37b inhibited TNF‐α‐induced interferon‐γ‐inducible protein (IP)‐10 expression significantly in human colonic SEMFs. Epithelial IL‐37b expression was increased in IBD patients, especially UC patients. IL‐37b may be involved in the pathophysiology of IBD as an anti‐inflammatory cytokine and an inhibitor of both innate and acquired immune responses.